Radiation and Magnetic Pressure Support in Accretion Disks Around Supermassive Black Holes and the Physical Origin of the Extreme-ultraviolet to Soft X-Ray Spectrum - Yan-Fei Jiang; Omer Blaes; Ish Kaul; Lizhong Zhang (The Astrophysical Journal, 2025)
We present the results of four 3D radiation magnetohydrodynamic simulations of accretion disks around a 10 ^8 solar mass black hole, which produce the far-ultraviolet spectrum peak and demonstrate a robust physical mechanism for producing the extreme-ultraviolet to soft X-ray power-law continuum component. The disks are fed from rotating tori and reach accretion rates ranging from 0.03 to 4 times the Eddington value. The disks become radiation pressure or magnetic pressure dominated, depending on the relative timescales of radiative cooling and gas inflow. Magnetic pressure supported disks can form with or without net poloidal magnetic fields, as long as the inflowing gas can cool quickly enough, which can typically happen when the accretion rate is low. We calculate the emerging spectra from these disks using multigroup radiation transport with realistic opacities and find that they typically peak around 10 eV. At accretion rates close to or above the Eddington limit, a power-law component can appear for photon energies between 10 eV and 1 keV, with a spectral slope varying between L _ν ∝ ν ^−1 and ν ^−2 , comparable to what is observed in radio-quiet quasars. A disk with a 3% Eddington accretion rate does not exhibit this component. These high-energy photons are produced in an optically thick region ≈30 ^∘ –45 ^∘ from the disk midplane, by compressible bulk Comptonization within the converging accretion flow. Strongly magnetized disks that have a very small surface density will produce a spectrum that is very different from what is observed.